2018
DOI: 10.1007/s13595-018-0690-1
|View full text |Cite
|
Sign up to set email alerts
|

Thinning affects microbial biomass without changing enzyme activity in the soil of Pinus densiflora Sieb. et Zucc. forests after 7 years

Abstract: & Key message Thinning increased microbial biomass but did not alter enzyme activities in the soil of Pinus densiflora Sieb. et Zucc. forests in South Korea. This effect of thinning was larger under a relatively heavy thinning intensity, but there was divergence in the magnitude between sites. & Context The balance between microbial biomass accumulation and enzymatic C and N assimilation determines the level of bioavailable C and N. However, the effects of thinning on these parameters remain contradictory and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 46 publications
(76 reference statements)
1
13
0
1
Order By: Relevance
“…Thinning can affect soil microbial structure and function by altering microenvironments (e.g., soil moisture and temperature), as well as the quality and quantity of substrate inputs (e.g., litter and roots), which can further influence soil P bioavailability [13]. Kim, et al [14] reported that thinning promotes the accumulation of microbial biomass, and is positively correlated with total soil C and N. Furthermore, this effect of thinning was found to increase with thinning intensity. Due to an increase in rainwater and a reduction of transpiration [15], soil moisture content in temperate broad-leaved deciduous forests [16], northern evergreen coniferous forests [17], and subtropical forests [18] was significantly higher in heavily thinned forest stands.…”
Section: Introductionmentioning
confidence: 99%
“…Thinning can affect soil microbial structure and function by altering microenvironments (e.g., soil moisture and temperature), as well as the quality and quantity of substrate inputs (e.g., litter and roots), which can further influence soil P bioavailability [13]. Kim, et al [14] reported that thinning promotes the accumulation of microbial biomass, and is positively correlated with total soil C and N. Furthermore, this effect of thinning was found to increase with thinning intensity. Due to an increase in rainwater and a reduction of transpiration [15], soil moisture content in temperate broad-leaved deciduous forests [16], northern evergreen coniferous forests [17], and subtropical forests [18] was significantly higher in heavily thinned forest stands.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Shen et al (2018) [14] observed increases in SOC, STN, and STP after thinning. Yang et al (2017) [11] and Kim et al (2018) [43] suggested a positive influence of thinning on the soil microbial biomass. We found the availability of soil nutrient contents also increased via the variation of understory environmental factors after thinning, as evidenced by higher SBD, SMC, ammonium nitrogen, nitrate nitrogen, and available phosphorus (Table 1).…”
Section: Variation Of Soil Properties and Stoichiometry Following Thimentioning
confidence: 99%
“…Soil microbial community activity increases when more decomposable organic matter is available, especially on the soil surface [49,58]. Therefore, taking thinning intensity, stand type, and restoration time into consideration is necessary to interpret the response mechanism of bacterial diversity to thinning activity [43].…”
Section: Variation Of Bacterial Composition and Diversity Following Tmentioning
confidence: 99%
“…forests, where the abundance of soil microbes increased significantly after seven years of thinning [44]. This is because thinning had increased carbon inputs from litter, root exudates, and dead fine root [43,44]. However, decreased soil microbial abundance in forest thinning had also been reported [11].…”
Section: Soil Microbial Community Structure and Soil Enzyme In Thinnimentioning
confidence: 99%